New Connectors for Joining Truss Beams to Vertical Stud Made of Thin-Walled Steel C-Profiles (Proceedings of Faculty of Civil Engineering, 2023)
The research that was conducted as part of scientific and development project UNIRI INOVA "New connector for joining structural elements made of thin-walled steel C-profiles" was presented. The project goal is to provide better knowledge about the behavior of new connection components for joining elements made of thin-walled steel C-profiles.
Keywords: thin-walled steel C-profile; laboratory tests; angle bracket; U-connector